Jovens e cidadania : privacidade e proteção de dados no contexto da cultura digital - Beppu, Flávia Renata (2022)
Privacy is an issue in evidence in the 21st century, due to the escalation of data processing through increasingly sophisticated technological resources. This research investigates privacy in the context of digital culture and aspects related to citizenship education in a society where citizens are constantly monitored through information and comunication technologies and other resources operated by large conglomerates at the service of companies and governments. The problem is to know how the lack of notions of privacy in the context of digital culture and the surveillance society can affect the exercise of citizenship by young people. The general objective is to understand young people's perception of privacy in digital culture and how this can contribute to their citizenship formation. The specific objectives aim to understand students' perception of privacy and data protection in digital culture and its implications, including the aspect of digital legacy; students' perception of citizenship in the context of societies permeated by digital culture; and the principles and values established by the Brazilian law for the protection of personal data in terms of privacy and personality rights. This is a descriptive research with a qualitative approach, which analyzed field data collected from a nonprobabilistic convenience sample, using a questionnaire instrument and conducting a focus group with integrated high school students from the Federal Institute of Mato Grosso. An analysis of the General Law for the Protection of Personal Data (LGPD) was also carried out, as well as research on dissertations and theses related to the investigated subject and theoretical reference to support this work, especially in Charlie Gere, Manuel Castells, Stéfano Rodotà, Massimo di Felice, Shoshana Zuboff, Hannah Arendt, André Lemos and Lúcia Santaella. As a result, it was observed that young people's perception of privacy is still more linked to the individualistic sense of secrecy and intimacy; and less to the collective perspective of control, transparency and informative selfdetermination. However, they begin to realize the implications of technology and digital culture in the field of privacy and, in this sense, the importance of protecting personal data as a way of preserving the private sphere of the individual and his social group, even after the death of users of digital service platforms. It was possible to verify the lack of knowledge of the LGPD and the legal concept of sensitive personal data, as well as the new rights related to protection and personal data. In addition, young people perceive little correlation between privacy and citizenship, which indicates that the group has an incipient notion about the dimension of privacy in the surveillance society. Finally, the students expressed great interest in the discussion of these themes at school, in an interdisciplinary way; still, they suggested some disciplines that, according to them, would make sense to deal with the subject. It is concluded, therefore, that there is a gap to be filled in the training of young people for citizenship in the context of digital culture and that education for privacy is presented as a way to guarantee freedom of conscience and legitimate democratic participation.